Making Wellington: earthquakes, survivors and creating heritage - McClean, Robert (Architectural History Aotearoa, 2012)
Landing at Te Whanganui a Tara in 1840, New Zealand Company settlers lost no time to construct the "England of the South" using familiar building materials of brick, stone, clay and mortar. Within months of settling at Pito-one (Petone), the newly arrived people not only experienced earthquakes, but also flooding of Te Awa kai Rangi (Hutt River). Consequently, the original plan to build the City of Britannia at Pito-one was transferred to Lambton Harbour at Pipitea and Te Aro. The construction of Wellington was severely disrupted by the first visitation occurring on 16 October 1848 when the Awatere fault ruptured releasing an earthquake of Mw 7.8. The earthquake sequence, lasting until October 1849, damaged nearly all masonry buildings in Wellington, including newly constructed Paremata Barracks. This event was soon followed by the 2nd visitation of 23 January 1855. This time it was a rupture of the Wairarapa fault and a huge 8.2 Mw earthquake lasting until 10 October 1855. Perceptions of buildings as "permanent" symbols of progress and English heritage were fundamentally challenged as a result of the earthquakes. Instead, the settlers looked to the survivors – small timber-framed buildings as markers of security and continued occupation. A small number of survivors will be explored in detail – Taylor-Stace Cottage, Porirua, and Homewood, Karori, both buildings of 1847 and both still in existence today. Also the ruins of Paremata Barracks as the only remnant of a masonry structure pre-dating 1848 in the Wellington region. There are also a few survivors of 1855 earthquake including Christ Church, Taita (1854) and St Joseph's Providence Porch, St Mary's College, Thorndon (1852). There are also the post-1855 timber-framed legacies of Old St Paul's Cathedral (1866), Government Buildings (1876) and St Peter's Church (1879). Improved knowledge about the historical evolution of perceptions of heritage in Wellington as a result of past earthquake visitations can help inform public education about heritage values, how to build today and strengthen existing buildings in readiness for future earthquake visitations.